Manusmrti : Gujarātī bhāshāntara : śāstrīya sandigdha vishayonāṃ vivaraṇa sahita - Manu (SAMP early 20th-century Indian books project ;, 1906)
Classical verse work on Hindu law; with translation and commentary.